Avaliação da reação de crianças submetidas à anestesia odontológica local com seringa convencional e com desenho externo modificado - Carvalho, Fernanda Matias de (2012)
Despite advances in Odontology, fear and anxiety regarding dentistry still affect a large number of people who, because of their fears, fail to seek treatment; this can result in low levels of oral health. The physical appearance of the instruments used by dentists seems to be a major cause of such fear and anxiety with regard to dentistry. The anesthetic syringe is the instrument that causes the strongest feelings of fear. So, the prevention of dental anxiety and patients fear should be one of the dentist’s highest priorities, this study aims to compare the reactions shown when children were anesthetized with a modified device and when they were anesthetized with a traditional syringe, and examine the results to see if a change in the external design of the anesthetic syringe can influence the levels of anxiety, fear and pain of patients. Sixty-four children aged 4-10 years were randomly assigned into two groups according to the device to be used in the first session of anesthesia. G1 (Traditional Syringe) and G2 (Modified syringe). Participants underwent two sessions and each patient was anesthetized with both devices. A single researcher performed anesthetic procedures, which were videotaped and the procedure consisted of infiltrative anesthesia in the posterior area of the maxilla. Due to the multidimensional nature of fear, anxiety and pain, a combination of tests was used to access them: Child Fear Survey Schedule - Dental Subscale - CFSS-DS, Facial Anxiety Scale-FAS, heart rate, the SEM scale Sound, Eyes and Motor, the Visual Analogue Scale (VAS) and the Frankl scale. These tests were applied in predefined situations as the waiting room (WR), the dental chair (DC), during the onset of anesthesia (OA) and end of anesthesia (EA). After the second session of anesthesia, children chose the device that they preferred. The results showed that most 78% children were classified as having a low level of anxiety (CFSS-DS). No significant difference was observed when comparing the traditional and modified devices. The syringe with a change in design was preferred by (57.8%) of the children. The anxious children reported more pain than non-anxious (p = 0.001) and their emotional state varied in different situations: WR, DC, OA and EA. (P <0.05). Thus, it was concluded that the appearance of the syringe is important, but not essential in order to control the anxiety, fear and pain which children suffer when undergoing dental anesthesia.